EFEKTIVITAS e-BOOK DALAM PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK - Rumiatun, Darti; Ismiyati; Yuningsih, Nani (Jurnal Medikes (Media Informasi Kesehatan), 2025)
In Asia, Africa and North America about 50% of children experience violence. While in Southeast Asia there are about 10% of boys and 15% of girls who have experienced one form of sexual violence in childhood. This research is a Quantitative research with a quasi-experimental pretest-post test design with control group. The research respondents were 4th and 5th grade elementary school students aged 9-10 years. The sample of the experimental group and the control group each amounted to 22 people. The intervention was given to students for 4 weeks. This research was conducted in 2 elementary schools, namely public and private elementary schools in the Lebak Regency area from July to August 2023. Data analysis used relationship test (Chi-Square) and T-test. The results showed that there was a significant relationship between children’s knowledge in preventing sexual violence against mother’s work (p-0.025). The data also showed a significant difference in the knowledge of the e-book group with the leaflet group with a value of p-0.000.